2021
DOI: 10.1007/s10723-021-09596-6
|View full text |Cite
|
Sign up to set email alerts
|

Secondary Pulmonary Tuberculosis Identification Via pseudo-Zernike Moment and Deep Stacked Sparse Autoencoder

Abstract: Secondary pulmonary tuberculosis (SPT) is one of the top ten causes of death from a single infectious agent. To recognize SPT more accurately, this paper proposes a novel artificial intelligence model, which uses Pseudo Zernike moment (PZM) as the feature extractor and deep stacked sparse autoencoder (DSSAE) as the classifier. In addition, 18-way data augmentation is employed to avoid overfitting. This model is abbreviated as PZM-DSSAE. The ten runs of 10-fold cross-validation show this model achieves a sensit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(8 citation statements)
references
References 38 publications
0
8
0
Order By: Relevance
“…A related study by Rajpurkar et al 5 used DenseNet-121 to develop novel architecture and reported a better performance than the prior baseline method presented in 8 . Several other works 9 , 10 also reported better performance using different advanced CNN models. After the outbreak of the recent pandemic in 2019, research efforts have redirected toward computer-aided detection (CAD) of respiratory diseases, including COVID-19 11 14 .…”
Section: Introductionmentioning
confidence: 78%
“…A related study by Rajpurkar et al 5 used DenseNet-121 to develop novel architecture and reported a better performance than the prior baseline method presented in 8 . Several other works 9 , 10 also reported better performance using different advanced CNN models. After the outbreak of the recent pandemic in 2019, research efforts have redirected toward computer-aided detection (CAD) of respiratory diseases, including COVID-19 11 14 .…”
Section: Introductionmentioning
confidence: 78%
“…During the enhancement, the DF is optimized with BFA, and the optimized DF is then integrated with the optimized HCF. For every PDL, the number of epochs is assigned as 200, and the search is allowed to stop when the specifed monitoring value is achieved [28][29][30][31].…”
Section: Deep Feature Mining Te Necessary Deep Featuresmentioning
confidence: 99%
“…In Li et al [33] , the author has leveraged the class and annotation information to train the CNN model and extract the features from local patch grids to detect and localize abnormalities. The author in [34] proposed an novel approach for identification of secondary pulmonary tuberculosis using Pseudo Zernike moment feature extractor and deep stacked sparse autoencoder and achieved an accuracy of 93.23% ± 0.81% and F 1 score of 93.23% ± 0.83%. Another work [35] presents rotation angle vector grid-based fractional Fourier entropy and deep stacked sparse autoencoder for accurate recognition of tuberculosis.…”
Section: Related Workmentioning
confidence: 99%